TWINNING INDUCED BY THE RHOMBOHEDRAL TO ORTHORHOMBIC PHASE TRANSITION IN LANTHANUM GALLATE (LAGAO3) - Wang W.L.; Lu H.Y. (My University, 2006)
Phase-transformation-induced twins in pressureless-sintered lanthanum gallate (LaGaO3) ceramics have been analysed using the transmission electron icroscopy (TEM). Twins are induced by solid state phase transformation upon cooling from the rhombohedral (r, R3̄c) to orthorhombic (o, Pnma) symmetry at ~45°C. Three types of transformation twins {101}o, {121}o, and {123}o were found in grains containing multiple domains that represent orientation variants. Three orthorhombic orientation variants were distinguished from the transformation domains converged into a triple junction. These twins are the reflection type as confirmed by tilting experiment in the microscope. Although not related by group-subgroup relation, the transformation twins generated by phase transition from rhombohedral to orthorhombic are consistent with those derived from taking cubic Pm3̄m aristotype of the lowest common supergroup symmetry as an intermediate metastable structure. The r→ o phase transition of first order in nature may have occurred by a diffusionless, martensitic-type or discontinuous nucleation and growth mechanism. © Springer-Verlag 2006.
Keywords: LAGAO; PEROVSKITE; PHASE TRANSITION; TWINS